Pos²: A Gui-Based Mini Point-of-Sale and Inventory Management System for a Mini Grocery Store (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Manual sales and inventory management in mini grocery stores often results in inaccurate calculations, delayed transactions, inconsistent stock monitoring, missing records, and difficulty in generating sales reports. To address these challenges, this study developed POS²: A GUI-Based Mini Point-of-Sale and Inventory Management System for a Mini Grocery Store. The system was designed to automate sales transactions, inventory monitoring, refund processing, product record management, activity logging, and sales report generation. It was developed using Python as the main programming language, Tkinter for the graphical user interface, and SQLite as the database management system. The system includes essential features such as PIN authentication, sales and checkout processing, product adding, viewing, updating, and deleting, stock adjustment, refund handling, activity log monitoring, and report generation. The SQLite database stores important information such as administrator accounts, inventory records, sales history, and activity logs, allowing data to remain available even after the application is closed. Through its graphical interface, users can manage store operations more easily without relying on handwritten records or manual computations. Testing showed that the system successfully performed its major functions with proper database integration. Overall, POS² provides a simple, organized, and efficient system that can help mini grocery stores improve transaction accuracy, inventory reliability, and business record management.